Checklist of earthworms (Oligochaeta: Lumbricidae) from Serbia: a review - Stojanović, Mirjana; Sekulić, Jovana; Trakić, Tanja (Zootaxa, 2018)
A checklist of the lumbricid earthworms in Serbia is presented. For the first time, comprehensive informations of all lumbricids in the country are given in order to establish the definitive list of known taxa from Serbia. The list underlines earthworm diversity and provides a general overview of their ecology, distribution in Serbia, and zoogeographical position. The complete list of earthworm taxa of Serbia comprises 74 species and subspecies of Lumbricidae, belonging to 15 genera. One third of earthworms in Serbia are endemics (26 taxa = 35.1%).